TEORI ELABORASI SEBAGAI STRATEGI PENGORGANISASIAN ISI MATERI PEMBELAJARAN MATEMATIKA - Hermansyah Hermansyah; Irianto Aras (Mathematics Education And Application Journal (META), 2019)
Prescriptive theory discusses the determination of learning methods to achieve predetermined learning goals. One aspect that must be considered is how to maintain student retention through rearranging learning materials. The characteristics of mathematics that are taught are arranged hierarchically so that appropriate strategies are needed to organize the content of learning material before it is delivered to students. One organizing strategy is elaboration theory, while the components of elaboration theory are elaborative sequences for the main structure of teaching, the sequence of prerequisites for learning, summary), synthesis, analogy, activating cognitive strategies), and learning controls.